Welfare effects of outsourcing in duopolistic markets - Jan König (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
This paper shows the strategic aspects of international outsourcing in a duopolistic market. Due to different costs of integrated production and outsourcing, the choice of a firm influences the strategy of the competitor via the output price. Therefore, the resulting market constellation depends on the fixed costs and the difference between marginal costs. We show that the three market constellations, both firms produce integrated, both use outsourcing and the firms operate with different strategies are possible. Also the welfare effects of the different outcomes are analysed. If the optimal firms decision is characterized by different strategies, this constellations for given costs is pareto superior to a constellation with equal strategies. On the other hand, for given costs, a resulting constellation of equal strategies can be pareto inferior or pareto superior to a constellation with different strategies.
Keywords: D43; L13; L22; L23; L24; 330; strategic outsourcing; oligopoly; welfare effects; Outsourcing; International; Duopol; Wohlfahrtseffekt; Theorie